Effect of Temperatures, Air Velocity and Flow Rate on Quality Attributes of Dried Cassava Chips - A. S., Ajala; G. O, Babarinde; S. J, Olatunde (Asian Journal of Agriculture and Rural Development, 2012)
In this work, cassava chips were dried in a tunnel dryer at temperature 600C, 700C and 800C using velocity 3.0m/s, 3.2m/s and 3.4m/s and load capacity of 7.5kg/m2, 10.0kg/m2 and 12.50kg/m2 as the drying variables. From the drying of experiments, data were generated to open up insights for the study and understanding of the physical parameters of the dryer as they affected the chips. The physical parameters studied in the dryer were air velocity, tray load capacity and air temperature. The effect of these drying parameters were evaluated on the quality attributes of the chips such as moisture content, bulk density, water absorption capacity, swelling capacity, residual cyanide content and colour. The results showed that drying temperatures and load rates had great effect on the quality attributes of the chips.